A Educação de Jovens e Adultos no IFPI, Campus de Picos: o PROEJA como política pública de inclusão educacional - Rocha, Natielly Granja (2022)
The present work results from the proposal of in-depth evaluation of the National Program for the Integration of Professional Education with Basic Education in the Modality of Youth and Adults (PROEJA), carried out within the Federal Institute of Education, Science and Technology of Piauí (IFPI), in the Campus de Picos, from the conceptions and meanings attributed by the subjects of the program, taking as a guide one of its fundamental principles of consolidation: the educational inclusion defended in its Base Document of 2007. PROEJA is guaranteed and legitimized in the law creating the Federal Institutes, Law nº 11,892, of December 29, 2008, which establishes the Federal Network of Professional, Scientific and Technological Education and establishes that at least 50% of the vacancies in these institutions must be designed to serve the high school public through integrated courses for students from elementary school, as well as the youth and adult education public. Based on this, PROEJA is analyzed on the Picos campus, considering the multiple relationships between the subjects involved. The historical, social, economic and political aspects that permeate the scenario and context of this reality are taken as fundamental elements, as well as the subjects and the relationships established within the institution, essential elements for the problematization of the object of this research. It is defined as a guiding question for the investigation: to what extent does PROEJA, an educational inclusion program, include its subjects from their respective points of view? The general objective of the research, which directs the theoretical-methodological process, is expressed in: understanding whether PROEJA on the Picos campus meets the principle of educational inclusion of the program's subjects. From this, specific developments are outlined: to present PROEJA and its results on the Picos campus; to identify the meanings and meanings attributed by PROEJA subjects regarding their inclusion character; and to analyze the practices of democratization of access and permanence of PROEJA students on the Picos campus. As a methodological perspective, an in-depth evaluation of public policies of a social nature is chosen, as proposed by Léa Rodrigues (2008), giving a political character to the evaluation (SILVA, 2012). To enable the achievement of the proposed objectives, bibliographic and documentary research is initially used, which makes it possible to know and identify the portrait and results of PROEJA on the Picos campus, addressing aspects of both completion and evasion to be observed in the documents . In addition, these quantitative data are used as a guide for the next stage, of empirical research, in which, through semi-structured interviews, it is possible to establish reflections and make final considerations about the meanings and senses attributed by PROEJA participants, among graduating students, dropouts and professionals, as a materialization of the objectives outlined in the research.